KEPERCAYAAN TERHADAP PERPINDAHAN MAKAM DI TANJUNG - Murjani Sani (Faculty of Ushuluddin and Humanities, 2014)
Describing where the moving tomb of Syekh Timur Tengah (hereinafter abbreviated as STT) in Tanjung. The removal of STT was through mediation with the tomb. This tomb is managed to perpetuate the relationship with STT’s spirit and the pilgrims. There is ‘haulan’ tradition in every 14 of Sha’ban, at that time HA is busy to communicate to the STT’s spirit, showing his encounter with the spirit of the dead in ‘conscious’ condition. According to al-Jauzi, the alive people can meet the spirit of the dead through dreams/ conscious based on the al-Zumar verse 42. It said that death is not lost but it is the separation of the body with the spirit. Their meeting is based on Ali ‘Imron verse 169-171 when he gets the blessing from Allah and when his brother who livedin the path of His. This is recognized by the Sufism as Liqa Barzakhi, as experienced by al-Tijani, it is out of ratio range. Meeting of HA and STT’s spirit is assumed as liqa Barzakhi, although it requires further study.